Pengaruh Perendaman Kolkisin Terhadap Pertumbuhan dan Produksi Tanaman Ciplukan (Phisalis angulata L.) - Ahmad Pratama (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
This study aims to determine the effect of soaking colchicine on the growth and production ofciplukan (Phisalin angulata L.) plants. This research was conducted by PT. Asam JawaPangarungan Village, Torgamba District. South Labuhanbatu Regency. The research was carriedout after the proposal seminar which began in February to June 2019. The research design usedwas a Non Factorial Randomized Block Design using 1 factor 3 treatment level, namely: K0 =ciplukan plants without colchicine, K1 = plants ciplukan with 0.25% colchicine for 24 hours, K2 =ciplukan with 0.625% colchicine for 24 hours, K3 = ciplukan with 1.25% colchicine for 24 hours.The parameters are Plant Height (cm), Leaf Width (cm), Flower Age Appears (days), Number ofPlanted Fruits, Planted Fruit Weight (grams). From some colchicine immersion (0.01%,0.025%, 0.05%) for 24 hours. The highest average plant height for 8 MST was found in theimmersion of 0.025%, 16.5 cm. The highest average leaf width for 11 MST was 0.025% soaking at16.17 cm. At the average age, the highest interest was found in the control, namely 41.4days. At the highest average number of fruits found in the immersion of 0.025%, 74 fruits. Thehighest average fruit weight was found in the immersion of 0.025%, 18.35%. So, from somecolchicine immersion treatment, the best is at 0.025% immersion.